Assessing the Effectiveness of the Functional Movement Screen in Predicting Noncontact Injury Rates in Soccer Players. Issue 12 (December 2017) - Smith, Paul D.; Hanlon, Michael P.
Abstract : Abstract: Smith, PD, and Hanlon, D. Assessing the effectiveness of the functional movement screen in predicting noncontact injury rates in soccer players. J Strength Cond Res 31(12): 3327–3332, 2017—This study assessed if the Functional Movement Screen (FMS) can accurately predict noncontact injury in adult soccer players when normalizing noncontact injury occurrence against match exposure levels. Senior male players ( n = 89) from 5 League of Ireland semiprofessional clubs participated in the study (mean age = 23.2 ± 4.4 years; mean height = 179.5 ± 6.6 cm; mean body mass = 77.5 ± 7.8 kg). Participants performed the FMS during preseason, and their injury occurrence rates and match minutes were tracked throughout 1 season. In total, 66 noncontact injuries were recorded. No significant difference was found in FMS composite scores between players receiving noncontact injuries and players not suffering a noncontact injury ( p = 0.96). There was no significant difference in exposure-normalized noncontact injury incidence between those scoring 14 or below and those scoring above 14 on the FMS (0.36 vs. 0.29 non-contact injuries per player per 1, 000 match minutes). Players scoring 14 or below on the FMS had an odds ratio of 0.63 ( p = 0.45; 95% CI = 0.19–2.07) of receiving a noncontact injury. Despite previous research showing links between low FMS composite scores and subsequent injury, these results suggest that the FMS cannot accurately predict a male soccer player's likelihood of receiving a noncontact injury and that a lower FMS composite score does not significantly increase their noncontact injury incidence rate per 1, 000 match minutes. Caution should therefore be used when using the FMS as a predictor of noncontact injury, and pain prevalence during the FMS, previous injuries, and training/match exposure levels should also be taken into account.